Spatial Variability and Geostatistical Mapping of Soil Physical Properties in Abia State Southeastern Nigeria (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
This study assessed the spatial distribution of selected physical properties of soils formed over three lithological materials—false bedded sandstone, coastal plain sands, and shale—in six locations across Abia State, southeastern Nigeria. Eighteen geo-referenced soil profiles were sampled and analyzed. Results showed that total sand content ranged from 240 to 890 g/kg, with the highest mean value (850 g/kg) in soils derived from coastal plain sands. Clay content varied widely from 90 to 680 g/kg, peaking in shale-derived soils. Bulk density increased with depth, ranging from 1.18 to 1.61 Mg/m³, while total porosity decreased accordingly, from 55.5% to 39.2%. Saturated hydraulic conductivity (Ksat) values were highest at the surface (up to 22.61 cm/hr) and declined sharply with depth to as low as 0.8 cm/hr, reflecting reduced macro-porosity. Silt-clay ratio ranged from 0.17 to 0.89, with higher values in soils over younger parent materials, indicating varying weathering intensities. Ordinary kriging was applied to interpolate unsampled areas, and model validation showed good predictive performance for bulk density (R² = 0.20; RMSE = 0.04), total porosity (R² = 0.05; RMSE = 2.39), and Ksat (R² = 0.57; RMSE = 2.63). The results highlight the influence of parent material and topography on soil variability and underscore the value of geostatistics for precision land management. These insights support data-driven decisions in crop selection, land use planning, and sustainable soil management across Abia State.